Relationship of Mean Platelet Volume and HbA1c in Predicting the Level of Diabetes Control in Type 2 Diabetes Mellitus - Varshini, Amrutha; K, Amita (Annals of Pathology and Laboratory Medicine, 2020)
Background: MPV is an indicator of platelet size and MPV is increased in DM as compared to non-diabetics, more so in presence of complications. There are few studies evaluating the association between MPV and HbA1c and its role in predicting glycaemic control with conflicting results. The present study was planned to determine the relationship between MPV and HbA1c in predicting the level of diabetes control in type 2 DM. Methodology: Cross sectional observational study including 100 consecutive cases of type 2 DM aged between 30 to 60 years. Mean platelet volume (MPV), platelet distribution width (PDW) and platelet count were obtained from fully automated haematology analyser Sysmex KX-21. Glycosylated haemoglobin (HbA1c) was analysed by automated haemoglobin analyser. Results: The mean age among 100 type 2 DM cases was 49.58 ± 14.49 years. The mean value of MPV and HbA1c was 10.25±0.90fl and 5.66± 1.17% respectively. There was no significant correlation found between MPV and HbA1c (r=0.110, p=0.275). Similarly, there were no significant association between MPV and three levels of glycaemic control. Conclusion: MPV is not a reliable marker for determining glycaemic control in type 2 DM.